The roles of protein ubiquitination in tumorigenesis and targeted drug discovery in lung cancer - Ye, Zhen; Yang, Jingru; Jiang, Hanming; Zhan, Xianquan (Frontiers in Endocrinology, 2023)
The malignant lung cancer has a high morbidity rate and very poor 5-year survival rate. About 80% - 90% of protein degradation in human cells is occurred through the ubiquitination enzyme pathway. Ubiquitin ligase (E3) with high specificity plays a crucial role in the ubiquitination process of the target protein, which usually occurs at a lysine residue in a substrate protein. Different ubiquitination forms have different effects on the target proteins. Multiple short chains of ubiquitination residues modify substrate proteins, which are favorable signals for protein degradation. The dynamic balance adapted to physiological needs between ubiquitination and deubiquitination of intracellular proteins is beneficial to the health of the organism. Ubiquitination of proteins has an impact on many biological pathways, and imbalances in these pathways lead to diseases including lung cancer. Ubiquitination of tumor suppressor protein factors or deubiquitination of tumor carcinogen protein factors often lead to the progression of lung cancer. Ubiquitin proteasome system (UPS) is a treasure house for research and development of new cancer drugs for lung cancer, especially targeting proteasome and E3s. The ubiquitination and degradation of oncogene proteins with precise targeting may provide a bright prospect for drug development in lung cancer; Especially proteolytic targeted chimerism (PROTAC)-induced protein degradation technology will offer a new strategy in the discovery and development of new drugs for lung cancer.